Cemental tear on the first maxillary premolar in the patient with facial palsy: an uncommon type of root fracture - Podugu, Uday Kumar; Balne, Tejasvi; Srivastav, Anushka; Ramana Reddy, K.V.; Ali, Mir Mujahed; Swathi, Aravelli (International Journal of Dental Materials, 2023)
A 56-year-old female patient came to the department complaining of pain in the upper right back tooth region. The patient reported a history of paralysis in the right half of the body. There is neither swelling nor inflammation in the gingiva. No sinus tract is present in the vestibular area. There were no noticeable caries lesions. Right first maxillary premolar with significant periodontal pocket and grade 2 mobility on palpation. There is tenderness in the percussion. The patient refused treatment alternatives and had the tooth extracted. The middle third of the root contains a completely detached fragment in the middle third. The root fragment was sent for biopsy for histological analysis. Cementum, dentin, and inflammatory cells were found during histological examination and were suggestive of cemental tear.